Invar Electroplating for Controlled Expansion Interconnects. (23rd August 2016) - Dubin, Val M; Lisunova, Milana O; Kovalenko, Igor O; Walton, Barbara L; Downey, Gillian; Su, Jonathan; Witt, Kevin
Abstract : NANO3D SYSTEMS ("NANO3D") has developed an electroplating technique to produce uniform, low-internal-stress and controlled-expansion nickel iron alloy (36 % of Nickel and 64% of Iron (INVAR)) films on various substrates to fabricate redistribution layers (RDL), through silicon vias (TSV) interconnects, pillars, bumps, pads and free standing foils. The linear thermal expansion of the INVAR deposits was measured down to 0.4 ± 0.1 (x10 -6, (K -1 )) within a process window that corresponds to the ultra-low internal stress (30±2 (MPa)) and uniform morphology (Ra ~ 2 (nm)). The thermal conductivity and specific heat capacity of the INVAR pinhole-free films were found to be in the range of 43 ± 5 (W/mK) and 0.45 ± 0.05 (J/gK), respectively. Ultra-high ductility of about 40 ± 10 % has been obtained for the free standing INVAR films, which possess the high tensile strength of 500 ± 60 (MPa) and yield strength of 280 ± 50 (MPa).